Physical vs augmented reality model: comparative study toward learning experiences at heritage studies gallery - Kassim, Mohd Hisyammudin; Abdullah, Fadzidah; Denan, Zuraini; Ahmad Arafat, Khandoker (2016)
The research focuses on the comparison of students’ learning experience between usage of physical models and Augmented Reality (AR) models of Islamic Heritage at Heritage Studies Gallery. Currently, the gallery has embedded mobile AR technologies as an alternative in collecting, and displaying the learning content. These mobile AR technologies work as a medium of interaction between the students and learning content. AR models are not going to replace the roles of physical models, but they are used to assist students’ learning by utilising 3D visualizing media especially for Islamic architectural heritage. Thus, the objective of this study is to compare the students’ perceptions of their learning experience between utilising physical models versus using AR models of Islamic Architectural Heritage. The research applied qualitative-quantitative mixed research approach, where the observation through video camera and questionnaires are used to obtain primary data. The survey on the students’ perception would be collected right after the students experience the learning process at the gallery. It is anticipated that AR models is preferable as compared to physical models in the context of the gallery display for learning experience. The reflection of this research, highlight the role of both learning objects as learning components that offer learning impact to the student learning experience.